2014
DOI: 10.1111/jpy.12198
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic stress modifies the synthesis of alpha‐tocopherol and beta‐carotene in phytoplankton species

Abstract: We performed laboratory experiments to investi-gate whether the synthesis of the antioxidants α-tocopherol (vitamin E) and β-carotene in phytoplankton depends on changes in abiotic factors. Cultures of Nodularia spumigena, Phaeodactylum tricornutum, Skeletonema costatum, Dunaliella tertiolecta, Prorocentrum cordatum, and Rhodomonas salina were incubated at different tempe-ratures, photon flux densities and salinities for 48 h. We found that abiotic stress, within natural ecological ranges, affects the synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…However, it was already demonstrated that H 2 DCF is oxidized by other ROS, including superoxide anion radical, hydroxyl radical, peroxyl, alkoxyl, hydroperoxyl and peroxynitrite which are products of normal metabolism (Halliwell and Gutteridge, 2007). Intracellular production of ROS does not necessarily imply cellular toxicity, but oxidative stress will occur when ROS formation exceeds antioxidant defense capability or disrupts redox signaling, affecting cell functionality (Häubner et al, 2014). DCF can be oxidized by various ROS including H 2 O 2 , organic hydroperoxides, nitric oxide and peroxynitrite (Gomes et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was already demonstrated that H 2 DCF is oxidized by other ROS, including superoxide anion radical, hydroxyl radical, peroxyl, alkoxyl, hydroperoxyl and peroxynitrite which are products of normal metabolism (Halliwell and Gutteridge, 2007). Intracellular production of ROS does not necessarily imply cellular toxicity, but oxidative stress will occur when ROS formation exceeds antioxidant defense capability or disrupts redox signaling, affecting cell functionality (Häubner et al, 2014). DCF can be oxidized by various ROS including H 2 O 2 , organic hydroperoxides, nitric oxide and peroxynitrite (Gomes et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Their concentration gives important information on the cell status controlling, for example, PSII activity and therefore photosynthesis and the expression of genes involved in acclimation and defence strategies (Foyer and Shigeoka, 2010). While in higher plants, much information on the antioxidative network is available (Mullineaux et al, 2000;Mittler, 2002;Logan et al, 2006;Sharma et al, 2012), little is known in microalgae Snoeijs et al, 2011;H€ aubner et al, 2014) and in diatoms (Rijstenbil, 2002;Affan et al, 2009;Van de Poll et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The production of pigments by N. oculata may differ significantly according to growth conditions and medium composition (Lubi an et al, 2000). Some investigations have shown an increase in carotenoid content of N. oculata cultured under low light incidence (H€ aubner, Sylvander, Vuori & Snoeijs, 2014;Rebolloso-Fuentes et al, 2001;Sukenik, Zmora & Carmeli, 1993). Similarly, high temperature favors accumulation of beta-carotene, as happens with other carotenoids (e.g., zeaxanthin) in N. oculata.…”
mentioning
confidence: 99%
“…Temperature plays an important role in microalgae metabolism, particularly in the accumulation/conversion of xanthophyll-cycle pigments (violaxanthin, antheraxanthin and zeaxanthin). In this context, some studies have shown that an increase in temperature induces the conversion of most part of violaxanthin to antheraxanthin and zeaxanthin in the xanthophyll cycle of Nannochloropsis (Gentile & Blanch, 2001;H€ aubner et al, 2014;Lubi an et al, 2000). Another important factor is culture age, according to Lubi an et al (2000) carotenoids concentration increase as the culture gets older, especially after reaching the stationary phase.…”
mentioning
confidence: 99%